La dislocació a la dreta en català i castellà: microvariació en la interfície sintaxi/pragmàtica - Villalba, Xavier (Caplletra. Revista Internacional de Filologia, 2007)
This article investigates the use of right-dislocation in Catalan and Spanish. We have measured the productivity of right-dislocation in a corpus of an original Catalan text and its Spanish translation regarding four variables: category, grammatical function, discourse function, and distance with respect to the antecedent. The analysis shows that right-dislocation is a marginal phenomenon in Spanish, not only from a quantitative (10 occurrences vs. 232 occurrences in the Catalan text), but from a qualitative point of view: right-dislocation in Catalan affects all the categories, grammatical functions, discourse functions, and distances with respect to the antecedent, whereas in Spanish it is restricted to nominals (SD and DEM) and sentences (SC), to subject and object functions, mainly to a the (re)introduction of a topic in the discourse, and to extreme distances (1 and 4). So then, in order to fulfill the tasks covered by right-dislocation in Catalan, Spanish must resort to other mechanisms —the placement of the dislocate in situ, its omission, or left-dislocation—, which suggests that the difference between these languages has to do with the different discourse management of the same collection of syntactic resources.